2020
DOI: 10.3892/mmr.2020.11154
|View full text |Cite
|
Sign up to set email alerts
|

Neuroprotective effect of tormentic acid against memory impairment and neuro‑inflammation in an Alzheimer's disease mouse model

Abstract: cognitive impairment and neuro-inflammatory responses are the distinctive characteristics of alzheimer's disease (ad). Tormentic acid (Ta) is one of the major active components of Potentilla chinensis and has been demonstrated to have anti-inflammatory properties. However, the potential effects of Ta on neuro-inflammatory responses and memory impairment in AD remain unknown. The present study investigated the therapeutic effect of Ta on neuro-inflammation, as well as learning and memory impairment in ad mice. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 38 publications
0
3
0
Order By: Relevance
“…Different studies (Cui et al, 2020; Jiang et al, 2020) showed that tormentic acid ( 71 ), isolated from R. multiflora , Potentilla chinensis , and Ocimum gratissimum , is capable to inhibit the secretion of IFN‐γ cytokine, COX enzyme, and NO production in LPS‐induced activated macrophages. IC 5O value for compound 71 was determined as 64.7 μM.…”
Section: Antiinflammatory Activity Of Natural Triterpenesmentioning
confidence: 99%
“…Different studies (Cui et al, 2020; Jiang et al, 2020) showed that tormentic acid ( 71 ), isolated from R. multiflora , Potentilla chinensis , and Ocimum gratissimum , is capable to inhibit the secretion of IFN‐γ cytokine, COX enzyme, and NO production in LPS‐induced activated macrophages. IC 5O value for compound 71 was determined as 64.7 μM.…”
Section: Antiinflammatory Activity Of Natural Triterpenesmentioning
confidence: 99%
“…Individuals with AD typically suffer from loss of learning ability and memory, impaired judgment and reasoning[ 6 , 7 ], and loss of analytical ability[ 8 ], which can seriously affect their quality of life. This imposes a heavy economic and psychosocial burden on the affected families and the society.…”
Section: Introductionmentioning
confidence: 99%
“…Phytochemical studies on P. chinensis have revealed the presence of triterpenoids, flavonoids, organic acids, and phenolic compounds [ 5 , 6 ]. Triterpenoids from P. chinensis have been shown to have anticancer, anti-inflammatory, neuroprotection, and hepatic injury attenuating effects [ 7 , 8 , 9 , 10 ]. Tiliroside—a flavonoid from P. chinensis —possesses antioxidant, anti-obesity, and antidiabetic properties [ 11 , 12 , 13 ].…”
Section: Introductionmentioning
confidence: 99%